Comparison of the Immunogenic Properties of Lactiplantibacillus plantarum Carrying the Mycobacterial Ag85B-ESAT-6 Antigen at Various Cellular Localizations - Wiull, Kamilla; Boysen, Preben; Kuczkowska, Katarzyna; Moen, Lars Fredrik; Carlsen, Harald; Eijsink, Vincent G. H.; Mathiesen, Geir (Frontiers in Microbiology, 2022)
The bacille Calmette-Guèrin (BCG) vaccine has been used for a century, nonetheless, tuberculosis (TB) remains one of the deadliest diseases in the world. Thus, new approaches to developing a new, more efficient vaccine are desirable. Mucosal vaccines are of particular interest, considering that Mycobacterium tuberculosis first enters the body through the mucosal membranes. We have previously demonstrated the immunogenicity of a recombinant Lactiplantibacillus plantarum delivery vector with TB hybrid antigen Ag85B-ESAT-6 anchored to the cell membrane. The goal of the present study was to analyze the impact of antigen localization in the immune response. Thus, we assessed two novel vaccine candidates, with the TB antigen either non-covalently anchored to the cell wall (LysMAgE6) or located intracellularly (CytAgE6). In addition, we compared two expression systems, using an inducible (LipoAgE6) or a constitutive promoter (cLipoAgE6) for expression of covalently anchored antigen to the cell membrane. Following administration to mice, antigen specific CD4+ T-cell proliferation and IFN-γ and IL-17A secretion were analyzed for lung cell and splenocyte populations. Generally, the immune response in lung cells was stronger compared to splenocytes. The analyses showed that the type of expression system did not significantly affect the immunogenicity, while various antigen localizations resulted in markedly different responses. The immune response was considerably stronger for the surface-displaying candidate strains compared to the candidate with an intracellular antigen. These findings emphasize the significance of antigen exposure and further support the potential of L. plantarum as a mucosal vaccine delivery vehicle in the fight against TB.